CORRELATION BETWEEN PERCEPTION ON CLINICAL LEARNING ENVIRONMENTS AND CAREER CHOICE ON CLERKSHIP STUDENTS IN FACULTY OF MEDICINE UNIVERSITAS SEBELAS MARET - Adinda Kharisma Apriliani; Eti Poncorini Pamungkasari; Amandha Boy Timor Randita (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2019)
Background: Needs of health workers, especially general practitioners, relatively high in Indonesia. Career choices among medical students are various, such as general practitioner, specialist, medical researcher, etc. Many factors affect medical students’ career choices, one of them is learning environments. This study aims to prove the correlation between clerkship students’ perceptions of clinical learning environments and their career choices.Methods: This research was an analytical observational research with cross sectional approach. The subjects were clerkship students who underwent clinical rotation. The samples were 178 clerkship students from all departments. They were chosen by probability proportional to size sampling. Every respondent was given career choices questionnaire and PHEEM questionnaire which has analyzed for its validity and reliability with α≥0,6 (α=0,826) and r≥0,30 (r=0,442). The result of this study was analyzed by Chi-square test and followed by Contingency Coefficient with 95% confidence level (α = 0,05). Result: The result showed that students’ perception of clinical learning environment “good but still need improvement” category was nearly the same as “plenty of problems” category. The result on the students’ career choices, most students choose clinical career. There was significant correlation between perception of clinical learning environment and career choices on clerkship students of medical faculty, Sebelas Maret University with p <0,05 (p= 0,018), x2 count (x2=5,625) > x2 table (x2=3,841) and also very weak correlation (C= 0,189).Conclusion: There was very weak correlation between perception of clinical learning environments and career choice on clerkship students.